Tectonic and Depositional History of Upper Cretaceous Tanjero Formations in Sulaymanya Area, NE-Iraq - Karim, Kamal Haji; Surdashy, Ali Mahmood (Sulaimani Journal for Pure and Applied Sciences, 2005)
The basin of (Upper Cretaceous) Tanjero Formation is combined (tectonically) with that of the underlying Shiranish Formation and named Upper Cretaceous Zagros Early Foreland Basin instead of previous miogeosyncline and trench. In this basin Tanjero Formation is deposited in the near shore area in front of southwest advancing positive land of Iranian plate. This near shore area is called Upper Cretaceous Depocenter, whereas, the underlying Shiranish Formation a summed to be deposited in the deeper central part of the basin, which is called Upper Cretaceous Basin Center. The advancing of the hinterland (Iranian plate front) is very clear from southwest position changing of the shelf for about 20km. The shelf of lower sequence was near the Iranian border during Upper Campanian while it migrated to the area around Chuarta and Mawat Towns during middle Maastrichtian. It was inferred that most part of the formation is deposited by forced regression during collision of Iranian and Arabian plate. During this regression both flysch and molasses facies are deposited.
Keywords: Tanjero Formation; Geologic history; Cretaceous tectonic; foreland basin; Zagros; Kurdistan geology; Sulaimaniya area; Shiranish Formation